Hybrid MPPT-based predictive speed control model for variable speed PMSG wind energy conversion systems - Mai N. Abu Hashish; Ahmed Ali Daoud; Medhat Hegazy Elfar (International Journal of Applied Power Engineering (IJAPE), 2022)
In this research, a predictive speed control (PSC) technique based on permanent magnet synchronous generators is proposed for variable-speed wind energy conversion systems (VS-WECS) (PMSG). The control approach that has been developed makes it possible to regulate mechanical and electrical variables concurrently within the context of a single cost function. The power converter will then use the optimum switching state that will result in the lowest possible cost function when it has been chosen. The maximum power point tracking (MPPT) algorithms used in the proposed control approach are combined in order to achieve optimum efficiency. As a direct result of this, the conventional cascade structure of proportional-integral (PI) controllers has been removed, which results in an improvement in the system's dynamic responsiveness. In addition, predictive current control, also known as PCC, is implemented on the grid-side converter, also known as the GSC, in order to accomplish decoupled grid current control. Using MATLAB/SIMULINK, we analyze the performance of the suggested control methods and compare it to the performance of a traditional PI speed controller. The findings demonstrated that the MPC controller is superior than the PI controller in terms of its ability to handle system dynamics.